Nanoparticle mediated non-covalent drug delivery() - Doane, Tennyson (2012)
The use of nanoparticles (NPs) for enhanced drug delivery has been heavily explored during the last decade. Within the field, it is has become increasingly apparent that the physical properties of the particles themselves dictate their efficacy, and the relevant non-covalent chemistry at the NP interface also influences how drugs are immobilized and delivered. In this review, we reflect on the physical chemistry of NP mediated drug delivery (and more specifically, non-covalent drug delivery) at the three main experimental stages of drug loading, NP–drug conjugate transport, and the resulting cellular drug delivery. Through a critical evaluation of advances in drug delivery within the last decade, an outlook for biomedical applications of nanoscale transport vectors will be presented.